2022
DOI: 10.3390/molecules27061972
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bioaccessibility of Bioactive Compounds from Rosehip-Enriched Corn Extrudates

Abstract: The rosehip (Rosa canina L.) fruit has gained researchers′ attention due to its rich chemical composition in vitamin C, phenols, carotenoids, and high antioxidant activity; meanwhile, polymers such as pea protein are generally recognized as exhibiting a protection role against the extrusion process. Corn snacks extrudates obtained by replacing corn flour with 10% R. canina powder (R) and 10% R. canina with pea protein (RPP) were evaluated for the physicochemical, textural, optical, and nutritional characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…Focusing on carbohydrates, among the static in vitro gastrointestinal digestion studies, from 2017 to 2023 first months (76 references), 33% of them used Infogest protocol with or without methodology variants (Egger et al., 2019 ; Igual et al., 2022 ; Iqbal et al., 2021 ; Lestido‐Cardama et al., 2022 ; Lin et al., 2021 ; Lucas‐González et al., 2021 ; Skalickova et al., 2022 ; Sousa et al., 2020 ; Varnaitė et al., 2022 ; Wei et al., 2020 ). The reported variants included a mix of RSIE with colonic fermentation (Aguirre‐Calvo et al., 2020 ; Bai et al., 2021 ; Chait et al., 2020 ; Liu, Li, et al., 2021 ), or mainly enzyme addition (Figure 5a ).…”
Section: Static In Vitro Digestion Methods Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on carbohydrates, among the static in vitro gastrointestinal digestion studies, from 2017 to 2023 first months (76 references), 33% of them used Infogest protocol with or without methodology variants (Egger et al., 2019 ; Igual et al., 2022 ; Iqbal et al., 2021 ; Lestido‐Cardama et al., 2022 ; Lin et al., 2021 ; Lucas‐González et al., 2021 ; Skalickova et al., 2022 ; Sousa et al., 2020 ; Varnaitė et al., 2022 ; Wei et al., 2020 ). The reported variants included a mix of RSIE with colonic fermentation (Aguirre‐Calvo et al., 2020 ; Bai et al., 2021 ; Chait et al., 2020 ; Liu, Li, et al., 2021 ), or mainly enzyme addition (Figure 5a ).…”
Section: Static In Vitro Digestion Methods Variantsmentioning
confidence: 99%
“…Focusing on carbohydrates, among the static in vitro gastrointestinal digestion studies, from 2017 to 2023 first months (76 references), 33% of them used Infogest protocol with or without methodology variants (Egger et al, 2019;Igual et al, 2022;Iqbal et al, 2021;Lestido-Cardama et al, 2022;Lin et al, 2021;Lucas-González et al, 2021;Skalickova et al, 2022;Sousa et al, 2020;Varnaitė et al, 2022;Wei et al, 2020).…”
Section: S Tati C In Vitro D I G E S Ti On Me Thod Variantsmentioning
confidence: 99%
“…The simulated fluids contained KCl, KH 2 PO 4 , NaHCO 3 , NaCl, MgCl 2 (H 2 O) 6 , (NH 4 ) 2 CO 3 , CaCl 2 , and HCL or NaOH for the pH adjustment of the stock solutions of simulated digestion fluids. The in vitro sample digestibility (IVD%) value was calculated as the difference between the initial sample and the undigested one; the obtained result was divided by the initial mass sample and multiplied by 100, as mentioned by [23,31].…”
Section: Simulated Gastrointestinal Digestionmentioning
confidence: 99%
“…In a recent study, Igual et al showed that an in vitro digestion process based on a static in vitro method such as COST INFOGEST network could be successfully used in evaluating the bioaccessibility of some bioactive compounds from the vegetable matrix [23].…”
Section: Introductionmentioning
confidence: 99%
“…Rosehip extract, derived from wild roses, is a valuable natural ingredient due to its richness in vitamins, minerals and antioxidants. It is particularly known for its high content of vitamin C, which helps to brighten the skin, neutralizes free radicals and contributes to improving skin tone [19][20][21]. Polyphenols and flavonoids found in plant extracts have been associated with health benefits, including protection against diseases such as cancer, diabetes and cardiovascular problems.…”
Section: Introductionmentioning
confidence: 99%